Effects Of Suckling Versus Weaning On Performance Of Primiparous Gir (Bos Indicus) Cows And On Growth Rate Of Their Calves - Ghodasara, S. N.; Murthy, K. S.; Gajbhiye, P. U.; Savsani, H. H. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Weaning is generally practiced in dairy and beef cattle for achieving better growth rates by giving balance feed in foreign countries. In indigenous dairy cattle it is necessary to evaluate the effect of weaning and suckling on calf growth parameters and reproductive performance of dams. Fifty eight primiparous Gir cows and their calves were taken in to consideration for the study of these two managemental system including disease resistance and its effect on milk yield and lactation length. Significant differences (P <0.05) were observed in average daily weight gain (0.320±0.011 vs 0.440±0.011 g), weekly body weight gain (2.21±0.080 vs 3.09±0.78 kg) and total weight gain after 3 months of study period (28.70±1.036 vs 40.18±1.019 kg) in favour of calves that sucked their dams. Among two groups of cows, lower incidence of mastitis was recorded in suckled as compared to weaned group of cows and diarrhoea was a less frequent problem in calves of suckling system. By suckling in Gir cows significantly more milk (1540.51±135.69 lit) could be harvested as compared to weaning group (992.27±257.57 lit). However, five cows in weaned group also attained exceptionally higher milk yield with greater lactation days. The mean calving interval (501.83±18.38 vs 407.90±16.89 days) and lactation length (338.03±23.45 vs 210.19±36.823 days) were significantly higher in suckled than the weaned cows. Therefore, it is necessary to evaluate these two managemental systems thoroughly for the economics of milk production and calf raising in indigenous primiparous Gir cows.